Peran Teknologi Informasi dalam Optimalisasi Fungsi Manajemen Risiko Perbankan Syariah - Izzaini, Muhammad Fadhil (Maliki Interdisciplinary Journal, 2025)
Islamic Banking, Technology, Information, Risk Management, OptimizationThe advancement of information technology has driven significant digital transformation in risk management practices in Islamic banking. This study highlights the contribution of technology to improving the effectiveness of risk management and the challenges and opportunities that arise in the process. The results show that the application of technologies such as big data analytics, artificial intelligence, and integrated risk management systems can accelerate decision-making and improve operational accuracy and efficiency. However, the application of digitalization also poses new risks, especially related to data security and cyberattacks. In addition to technical aspects, the readiness of human resources, organizational culture, and compliance with regulations are important factors in supporting successful implementation. This research proposes a technology-based risk management optimization framework that is aligned with sharia values and global governance standards. It is expected that the results of this research can make a strategic contribution in strengthening the competitiveness and sustainability of Islamic banking in the digital era.